MANIPULATION OF MULTIMEDIA COMPUTER WITH GLPRO VERSION 7.0 - Faried Amfasya; Eko Hadijanto, SSI, MMSI (Jurnal Sistem Informasi, 2002)
The development of computers has now led to a more integrated system known as the Multimedia is a merger between the computer with a device that allows to ask, record, manipulate the images / video and high-quality audio into a two-way communication on a computer. For it is often necessary to find an audio-visual to make a presentation, build a homepage is also absolutely need these visual audio files, so on this occasion the author tries to discuss about GLPRO multimedia and programming with version 7.0. So the main problem adopted in this paper is to combine images and sound files so that becomes a visual audio files.